Upaya Peningkatan Budaya Kerja Yang Akuntabel dan Transparan di PT FJM - Lukiyana, Lukiyana; Putra, Bagas Kautsar Azizal; Reza, Bobby; Ridhwan, Muhammad (Jurnal Pemberdayaan Nusantara, 2025)
The Internship Program is a means for students to develop their competencies. Under the guidance of lecturers and supervisors at the internship location, lecturers and students work together to implement a good work culture. In the internship activities at PT FJM, the work culture implemented includes an accountable work culture and a transparent work culture. Through the internship program that has been prepared by lecturers and students, all accountable and transparent indicators are practiced in internship activities. The implementation of internship tasks that prioritize an accountable and transparent culture is expected to have a positive impact on the Company where the internship is held. The internship is carried out in the finance division to find out the financial processes that occur in the company. This internship program uses the project-based learning method, which is a project-based learning method that will be guided by the supervising lecturer and internship supervisor from the company.